Analisis efektivitas penerapan pembelajaran daring pada masa pandemi di SMPN 1 PPU - Idris, Muhammad Sofyan; Surmiati; Darmansyah (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Online learning is one of the main options in carrying out learning during the COVID-19 outbreak period which is a recommendation from the government not to do face-to-face. This condition makes SMP Negeri 1 PPU choose google classroom in conducting online learning. Google classroom is one of the online learning media that suits the needs of online learning today. This research aims to find out the effectiveness of online learning in SMP Negeri 1 PPU during the pandemic using Classroom, the results of the analysis will be used as a consideration in choosing an effective online learning media.This research is included in quantitative research that requires information based on data obtained through data collection through observations and questionnaires shared with respondents. The results of this study state that online learning using google classroom used today is effective. Google classroom is said to be effective because this application is very suitable for teachers in doing learning and has supporting features in online learning.The use of this application is very easy to learn and understand, save in the use of internet quotas and the use of this application may still be used in normal conditions. From the results of research on the effectiveness of online learning using google classroom is very effective. It is expected to continue to improve online learning during the COVID-19 pandemic by coordinating between teachers and principals.